2001
DOI: 10.2527/2001.7941011x
|View full text |Cite
|
Sign up to set email alerts
|

Tasco-Forage: I. Influence of a seaweed extract on antioxidant activity in tall fescue and in ruminants.

Abstract: Seaweed (Ascophyllum nodosum) is a known source of plant growth regulators, and application to turfgrasses has increased activity of the antioxidant superoxide dismutase (SOD) and specific vitamin precursors. Increased antioxidant activity in both plants and animals diminishes oxidative stress. Two pasture experiments investigated effects of Tasco-Forage (a proprietary seaweed-based product) applied to tall fescue (Festuca arundinacea) on antioxidant activity in plants and in ruminants that grazed the forage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 0 publications
6
71
1
1
Order By: Relevance
“…It has also been understood that heat stress impairs intestinal barrier integrity and causes leaky gut, which explains its negative effects on animal health and production (30). Algae have been found to protect the body from oxidative stress and to scavenge peroxides in immune cells (3,4). The MDA, GPx activity, and LPS-BP are considered useful biomarkers to assess the extent of heat stress in blood and tissue in mammals (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been understood that heat stress impairs intestinal barrier integrity and causes leaky gut, which explains its negative effects on animal health and production (30). Algae have been found to protect the body from oxidative stress and to scavenge peroxides in immune cells (3,4). The MDA, GPx activity, and LPS-BP are considered useful biomarkers to assess the extent of heat stress in blood and tissue in mammals (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that seaweed extract increases tolerance to oxidative stress and protects against adverse environmental conditions by enhancing the activity of the antioxidant enzymes SOD and Ascorbate peroxidase (ASP) [16] [72]. Potassium plays a key role in plants through the activation of enzymes by stabilizing the pH between 7 and 8 and changing the conformation of enzymes by binding to their surfaces [73].…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
“…Seaweeds have been reported to possess plant-growth promoting activity which made them relevant in agriculture and horticulture as organic fertilizers [15]. Fike et al [16] reported that seaweed extract derived from A. nodosum contains various compounds including amino acids and micronutrients. The application of Seaweed extract on vegetables and forage grasses increased root length, leaf area, and root and shoot biomass in response to drought stress, in addition to increasing chlorophyll and carotenoids [17].…”
mentioning
confidence: 99%
“…These results support the findings of Mansori et al (2015), who reported that the extract of Fucus spiralis and Ulva rigida decreased the MDA level in leaves of water-stressed Phaseolus vulgaris plants. Fike et al (2001) demonstrated that protective anti-stress effect of seaweeds may be associated with cytokinin activity, which mitigate stress-induced free radicals by direct scavenging of ROS and by inhibiting xanthine oxidation preventing ROS formation. Also, H. opuntia extract is rich in mineral nutrients as calcium, which has a specific role in controlling membrane structure and function by binding to phospholipids that stabilizes lipid bilayers and thus provides structural integrity to cellular membranes against oxidative damage (Hirschi, 2004).…”
Section: Discussionmentioning
confidence: 99%